The role of adjuvant chemotherapy in resected stage I non - small cell lung cancer: A Turkish Oncology Group Study - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2021)
Purpose: The benefit of adjuvant chemotherapy for tumors smaller than 4 cm is not clear. We aimed to evaluate the prognostic impact of adjuvant platin-based chemotherapy in high-risk stage I patients with non-small cell lung cancer (NSCLC). Methods: This cooperative group study included 232 NSCLC patients who underwent curative surgery for stage I disease with tumor size 2-4 cm. Results: Median age at presentation was 63 years (range 18-90). The mean tumor size was 29.6 +/- 7.3 mm. The frequency of patients with specified risk factors were: visceral pleural effusion (VPI): n: 82 (36.6%); lymphovascular invasion (LVI): n: 86 (39.1%); Grade 3: n: 48 (32.7%); Solid micropapillary pattern (SMP): n: 70 (48.3%). Adjuvant platin-based chemotherapy was administered to 51 patients. During a median follow-up period of 50.5 months 68 patients (29.3%) developed recurrence, 54 (23.3%) died from any cause and 38 (16.4%) of them died of lung cancer. Patients who received chemotherapy compared with the non-chemotherapy group had a longer 5-years relapse-free survival (RFS) (84.5 vs. 61.1%). Also on multivariate analysis, adjuvant chemotherapy was a significant independent prognostic factor for RFS. Conclusion: Adjuvant platin-based chemotherapy should be considered for patients with small tumors with adverse risk factors.
Keywords: adjuvant chemotherapy; lung cancer; oncology; lymphovascular invasion; solid-micropapillary pattern; platinum-based therapy; VISCERAL PLEURAL INVASION; PROGNOSTIC-FACTORS; INTERNATIONAL ASSOCIATION; LYMPHOVASCULAR INVASION; INDEPENDENT PREDICTOR; TNM CLASSIFICATION; VESSEL INVASION; POOLED ANALYSIS; TEGAFUR-URACIL; 7TH EDITION